(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Olaru Y. Communicative training of future economists in the creative approach to learning in the process of studying the humanities. The article is an attempt to reveal the features of communication training for future economists in the context of a creative approach to learning in the study of the humanities. Substantiated the relationship of the creative component of personal education of future professionals in economics education сreative communicative learning environment.